(3JYHjQ GdQDjGs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GeG HYO adeG cGfJ GdcJH GdeUfaI ai GdQDjG hGdJYHjQ ddeJbOejf hGdeJCNQjf ef GdjhfGfjI hGdYQH cKjQI s
(3BNQgG (B:s
(3djchf YhfkG def jQjO GSJNQGL GdQDjG GdZQjHI GdNajI jJhSWgG hEP bO hajfG HeG hYOfG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B125 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdBUajI HMjOQ CHGO HGdgfO (B((3eLGejY (B41) s
Keywords: (3JYHjQ GdQDjGs